Gendered culture in peacekeeping operations - Carreiras, H. (International Peacekeeping, 2010)
This article examines the way that gender values and norms underlie the definition and development of peacekeeping missions, and how, in turn, these might contribute to changing prevailing gender regimes within military forces. The article starts with a revision of the gendered nature of the military, brings in the topic of changing professional identities in modern armed forces, and proceeds with an examination of key issues and contradictions in contemporary discourses on gender and peacekeeping. Based on empirical evidence from a variety of research projects conducted since the early 1990s, and with a special focus on the role and integration of women soldiers in peacekeeping, it questions the extent to which peacekeeping missions, and specifically what has been labelled a new gender regime in peacekeeping, have the potential to challenge previously dominant conceptions and practices of gender roles in military culture. The article stresses the idea that only a context-sensitive analysis will allow us to adequately account for and understand the gender dimension of peacekeeping culture.